A Clay Ball with a Cypro-Minoan Inscription from Tiryns - Vetters, Melissa (Archäologischer Anzeiger, 2014)
A clay ball with a Cypro-Minoan inscription excavated in a LH IIIC Developed workshop context at the northern tip of Tiryns’ Lower Citadel forms the basis for this discussion on interaction patterns and contacts between Mycenaean Tiryns and Late Bronze Age Cyprus. To provide a background to the contextual assessment of the Tiryns clay ball documents, contexts and practices associated with the Cypro-Minoan script/s on Cyprus are discussed. The analysis of the Tiryns clay ball focuses on epigraphy, find context and the dating of the object. While it is impossible to establish the provenance of the clay ball on the basis of current evidence, stratigraphic details and its find spot within a workshop area point to a post-palatial date. An overview of East Mediterranean (especially Cypriot) objects found in Tiryns identifies a few areas where such artefacts occur more frequently and discusses implications of ›Cypriot‹ practices on the basis of contextual data. Intimate contacts between Tiryns and Cyprus are attested to during the late palatial period, but continue into the postpalatial period and point to interpersonal contacts rather than merely long-distance trade.